Fascism, liberalism and Europeanism in the political thought of Bertrand de Jouvenel and Alfred Fabre-Luce - Knegt, Daniel (Amsterdam : Amsterdam University Press, 2017)
Despite the recent rise in studies that approach fascism as a transnational phenomenon, the links between fascism and internationalist intellectual currents have only received scant attention. This book explores the political thought of Bertrand de Jouvenel and Alfred Fabre-Luce, two French intellectuals, journalists and political writers who, from 1930 to the mid-1950s, moved between liberalism, fascism and Europeanism. Daniel Knegt argues that their longing for a united Europe was the driving force behind this ideological transformation-and that we can see in their thought the earliest stages of what would become neoliberalism.
Machine generated contents note
Series number at top of spine
Includes bibliographical references (pages 267-280) and index.